Quantitative analysis of e-health's impact on health systems - Alqurashi, Heba (Frontiers in Digital Health, 2025)
BackgroundThis study evaluates the impact of e-health solutions on healthcare systems, focusing on how the perceived usefulness of these technologies affects healthcare workers’ intentions to use them.MethodsThe study used a cross-sectional approach in the form of a close-ended questionnaire to collect quantitative data from a sample of 130 healthcare professionals randomly selected. The collected data was then analyzed using SPSS version 30, statistical analysis was utilized such as frequency test, reliability analysis, and correlation coefficient analysis.ResultsThe findings suggest a statistically significant correlation between attitudes toward e-health and intention to use, with a moderate effect. The implementation of e-health technologies has a positive impact on healthcare management, though the magnitude of the effect varies depending on the technology and context and prior computer expertise significantly influences health workers’ attitudes toward adopting and using e-health.DiscussionE-health technologies can significantly improve operational efficiency, reduce costs, and enhance the quality of care in healthcare system. Successful implementation requires careful planning, investment in infrastructure, addressing security concerns, and training of healthcare professionals.